Towards energy-efficient mobile ad optimization: an app developer perspective - Ahmad Raza Hameed; Saif Ul Islam; Ahmad Almogren; Hasan Ali Khattak; Ikram Ud Din; Abdullah Gani (MDPI AG, Basel, Switzerland, 2020)
Advertising over smart devices is one of the growing trends in the information technology domain. Most of the Android application (app) developers generate revenue through the use of ads, but on the other hand, the end users get the free app. However, the excessive number of ads infers hidden costs with respect to energy consumption, network utilization, and user comfort. These factors affect the app rating and reviews. Consequently, developers require a technique to balance app performance through optimized mobile ad usage. Therefore, in this paper, we extend an existing work and propose an energy-efficient method that uses gamma correction to reduce the hidden costs of a mobile app. In this approach, gamma correction efficiently balances the app performance by minimizing the size of ads. The size of the mobile ad is reduced by adjusting its pixels, reducing background color, and illuminating the content of the ad. After several experiments, it is deduced that our proposed approach efficiently saves mobile battery and developers can apply this approach to improve app rank and feedback.